Multiplication and division of fraction

Multiplication of Fractions

The product of the two fractions a/2 and c/d is defined in previous Chapter to be (ac)/(bd);

that is,  a/b*c/d=(ac)/(bd) 

Thus the product of two fractions is a fraction whose numerator is the product of the numerators and whose denominator is the product of the denominators. In general,

     Product of two fractions

Note    Always reduce the resulting fraction to lowest terms.


EXAMPLE  Find the product of (27a^3b^2)/(8x^2y) and (16x^3y)/(81a^2b^3)



Note     It is easier to reduce (27*16)/(8*81) then 432/648, which is the result of the products.

That is. numbers should not be multiplied together until the fraction has been simplified.

To multiply fractions whose numerators or denominators are polynomials, first factor polynomials completely Consider the fractions as just one fraction, and divide the numerators and denominators by their greatest common factor to get an equivalent fraction in lowest terms.


Let’s see how our Algebraic Solver this and similar expressions. Click on "Solve Similar" button to see more examples.  


EXAMPLE  Simplify (x^2-3x)/(2x^2+11x+5)*(6x^2+x-1)/(3x^2-10x+3)


       Reducing the Fraction to its lowest term

EXAMPLE  Simplify (12x^2-13x+3)/(3x^2-5x-2)*(2x^2-x-6)/(9-6x-8x^2)






Division of Fractions

  From the definition of division of fractions, discussed before, we have

     a/b ÷ c/d = a/b*d/c

  The above result shows how to transform division of fractions into multiplication of fractions.

  The fractions c/d and d/c are called multiplicative inverses or reciprocals

Note   The reciprocal of the expression a+b is 1/(a+b, not 1/a+1/b

Note   The reciprocal of 1/a+1/b is 1/(1/a+1/b), or simplified, ab/(b+a)



EXAMPLE  Simplify (3a^3)/(5b^2) ÷ (9a^2)/(20b)

Solution   (3a^3)/(5b^2) ÷ (9a^2)/(20b)== ((3a^3)/(5b^2)) *((20b)/(9a^2))== (4a)/(3b)

Note  Note The difference between

        a/b÷ (c/d*e/f) == a/b*d/c*e/f == ade/bcf 


       a/b÷(c/d*e/f)== a/b ÷ ce/df== a/b*df/ce== adf/bce



EXAMPLE  Simplify (9a^2b^4)/(49x^2y^3) ÷ (a^2b)/(14x^2y)*(21y)/(ab^2)


(9a^2b^4)/(49x^2y^3) ÷ (a^2b)/(14x^2y)*(21y)/(ab^2)==(9a^2b^4)/(49x^2y^3)*(14x^2y)/(a^2b)*(21y)/(ab^2)==(54b)/(ay)


EXAMPLE  Simplify (a^3b^2)/(x^2y^3) ÷ ((a^2b^5)/(x^5y)*(x^3y^2)/(ab^3))


(a^3b^2)/(x^2y^3) ÷((a^2b^5)/(x^5y)*(x^3y^2)/(ab^3))==((a^3b^2)/(x^2y^3)) ÷ ((a^2b^5*x^3y^2)/(x^5y*ab^3))==(a^3b^2)/(x^2y^3)*(x^5y*ab^3)/(a^2b^5*x^3y^2)==a^2/y^4



EXAMPLE  Simplify (8x^2+2x-3)/(4x^2-17x-15) ÷ (12x^2-20x+7)/(6x^2-37x+35)

Solution    As in multiplication of fractions, we factor the numerators and denominators  

        Factoring numerator and denominator


Let’s see how our Algebraic math solver solves this and similar expressions. Click on "Solve Similar" button to see more examples.  


← Previous Tutorial Next Tutorial →